Power and trust in organizational relations: an empirical study in Turkish public hospitals - GÜRBÜZ, FATMA GÜLRUH (WILEY, 2015)
Given the salience of the interplay between trust and power relations in organizational settings, this paper examines the perceptions of social power and its effects on trust in supervisors within the context of public hospitals. Following the theoretical background from which the study model is developed, the recent situation of hospitals within Turkish healthcare system is discussed to further elucidate the working conditions of physicians. Sample data were collected employing a structured questionnaire that was distributed to physicians working at seven different public hospitals. The statistical analyses indicate that perceptions of supervisors' social power affect subordinates' trust in supervisors. Although coercive power is found to have the greatest impact on trust in supervisors, the influence of the power base is weak. In addition, the results show that perceptions of social power differ between genders. However, the results do not support any of the hypotheses regarding the relations between trust in supervisors and the examined demographic variables. Copyright (c) 2014 John Wiley & Sons, Ltd.
Keywords: supervisor-subordinate relationship; trust in supervisor; social power; public hospitals; SATISFACTION; BASES; MANAGEMENT; TURKEY; REWARD; MODEL